2005
DOI: 10.1155/ijrm.2005.53
|View full text |Cite
|
Sign up to set email alerts
|

Unbalance Response Prediction for Rotors on Ball Bearings Using Speed‐ and Load‐Dependent Nonlinear Bearing Stiffness

Abstract: Rolling-element bearing forces vary nonlinearly with bearing deflection. Thus, an accurate rotordynamic analysis requires that bearing forces corresponding to the actual bearing deflection be utilized. For this work, bearing forces were calculated by COBRA-AHS, a recently developed rolling-element bearing analysis code. Bearing stiffness was found to be a strong function of bearing deflection, with higher deflection producing markedly higher stiffness. Curves fitted to the bearing data for a range of speeds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Later they proposed an adaptive active balancing strategy for suppression of vibration in accelerating rotors [7]. There were additional studies on accelerated rotors whose main aim was to investigate methods for reducing the maximum amplitude of lateral response during acceleration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Later they proposed an adaptive active balancing strategy for suppression of vibration in accelerating rotors [7]. There were additional studies on accelerated rotors whose main aim was to investigate methods for reducing the maximum amplitude of lateral response during acceleration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is substantial power loss reduction with only minor impact on load carrying capacity, component size and weight and noise generation. Adequate compro mises have to be proposed [2] .…”
Section: Literature Review On Worm and Worm Gearboxmentioning
confidence: 99%
“…Vazquez et al [2] have been studied the effects of bearings mounted on flexible supports on the dynamic response and critical speed and they concluded the cross coupling coefficients does not have a large effect on the dynamic response and critical speed. David et al [3] study the effect of using roller bearings on the vibration amplitude of rotor and they concluded that damping will significantly decrease the rotor vibration amplitude. Kang et al Navarro et al [4], Have been used an active scheme of unbalance compensation for a rotor-bearing system by apply two of control strategies together, and these strategies are rotor speed acceleration scheduling and dynamic bearing stiffness controller.…”
Section: Introductionmentioning
confidence: 99%